2022
DOI: 10.1097/moo.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis of the face: current concepts in cause, diagnosis and management

Abstract: Purpose of review Necrotizing fasciitis of the face is uncommon but potentially life threatening. With adequate multidisciplinary treatment, mortality and has significantly improved. This article highlights current concepts and supporting literature in the management of facial necrotizing fasciitis. Recent findings Management of necrotizing fasciitis involving the face requires a multisciplinary team approach, including early medical and surgical interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Often, close monitoring and repeat debridement is required, with reconstructive options viable only after source control has been obtained. [ 13 ] Some retrospective studies, case-controlled studies, and small randomized trials have also suggested intravenous immune globulin (IVIg) therapy as an additional option in the treatment of NF [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Often, close monitoring and repeat debridement is required, with reconstructive options viable only after source control has been obtained. [ 13 ] Some retrospective studies, case-controlled studies, and small randomized trials have also suggested intravenous immune globulin (IVIg) therapy as an additional option in the treatment of NF [ 14 ].…”
Section: Discussionmentioning
confidence: 99%